Water Woes of Women: Obstacles to Gender Equity under Changing Climate - Jagriti Kher , Savita Aggarwal and Geeta Punhani (Indian Journal of Extension Education, 2018)
Women are very closely associated with water since it is at the core of their traditional household responsibilities.Studies conducted across developing countries have shown that water collection still remains a highly genderedtask. Provision of safe water for the household is one of the Practical Gender Needs (PGNs) of women, whichin turn is crucial to enable them to meet their Strategic Gender Needs (SGNs) such as education, and controlover resources. While the requirements of water are continuously increasing due to demographic, socioeconomic and technological changes, the availability of water faces a serious threat from human inducedclimate change. If the gender-based inequalities and inequities in society have to be reduced, it is very importantto invest in water supply and sanitation related infrastructure at the household level. Besides improving theirquality of life, such investment will enhance women’s adaptive capacity to face climatic stresses and extremes.